Meningkatkan Pemahaman Siswa dalam Cerita Fabel melalui Metode Pembelajaran Role Playing pada Siswa Kelas 3 Sekolah Dasar - Kusnadi, Auril Ramadani; Putri, Cici Dena; Yusuf, Rinaldi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to improve the understanding of fable stories among third-grade students at SDN Rawasalak through the implementation of the Role Playing learning method. The background of this research is based on the low ability of students to comprehend elements of fable stories—such as characters, plot, and moral messages—as indicated by the results of the pretest and initial observations. The study adopts a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, consisting of two cycles. Data were collected through reading comprehension tests, observation sheets, and teacher reflections. The results show an increase in the students’ average scores from 67.8 in the pre-cycle to 78.1 in the second cycle, as well as an improvement in learning mastery from 37.5% to 87.5%. Moreover, student engagement in the learning process also increased significantly. These findings indicate that the Role Playing method is effective in enhancing students' comprehension of fable stories while fostering an active, enjoyable, and meaningful learning environment. This method is recommended as an alternative instructional strategy for teaching Indonesian language in elementary schools.